TRANSFORMASI PERAN INTERNAL AUDITOR DAN PENGARUHNYA BAGI ORGANISASI - Sigit Eko Pramono (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
Organizations underpressure to manage businessrisks are increasingly relying on the role of internal auditor for help in achieving these objectives. Internal auditors are meeting to challenge to add value in various ways. Their strategies include transforming their role to bring the auditing function closer to management needs. This transformation cannot occur unless the auditor and the all level of management start to think differently about the role of internal auditor. Changing current paradigms, adding training and hiring new personnel may be required to achieve these goals.